Do Urban Social Enterprises Benefit from Agglomeration? Evidence from Four UK Cities. Issue 8 (2nd August 2016) - Pinch, Steven; Sunley, Peter
Abstract : Pinch S. and Sunley P. Do urban social enterprises benefit from agglomeration? Evidence from four UK cities, Regional Studies . This paper examines the relevance of clustering theory for an understanding of the location of social enterprises (SEs). This is accomplished through an analysis of the extent to which managers of SEs in four major UK cities perceive themselves to benefit from agglomeration effects. The paper concentrates on two broad sets of agglomeration processes: the first is Marshallian externalities and Porter's cluster processes; and the second set includes urbanization economies and local institutional relationships. The study suggests the key benefits of agglomeration to SEs are that it enables access to demand for SE goods and services together with institutional support, funding and commercial contracts, as well as access to both formal and informal networks that can provide a wide range of knowledge and mutual support. It was, however, difficult to find direct evidence to support the importance of the Marshall–Arrow–Romer (MAR)-type spillovers related to labour market pooling, the efficient procurement of indirect inputs or localized knowledge spillovers.